TELAAH TEKNOLOGI INFORMASI DAN SISTEM INFORMASI DALAM ORGANISASI DENGAN LINGKUNGAN : Suatu Kajian Teori - Agustika, Fitriah; Siregar, Sadrak; Obara, Dony; Paramarta, Vip (JURNAL BISNIS KOLEGA, 2023)
The purpose of this research is to describe the use of information technology and information systems in organizations with the environment. This research is a literature review, with a descriptive approach. The results of the theoretical analysis and studies of relevant previous studies are that information technology can be placed/treated as a mediating (intervening) variable in the relationship between environmental attributes and organizational structure attributes. This is due to the high level of utilization/use of information technology in companies and the application of information technology is an important requirement in managing the company's business activities. The role of technology in the relationship between environmental attributes and organizational structure attributes is information technology as a mediator in this relationship. Information technology has become an important element in achieving organizational goals to overcome environmental uncertainties. The existence of information technology is needed to create the structural response desired by management in anticipating environmental changes